Islam Nusantara: The Conceptual Vocabulary of Indonesian Diversity - Schäfer , Saskia (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2021)
This article examines recent debates surrounding Islam Nusantara within contemporary Islamic discourses in Southeast Asia, particularly in Indonesia, and assesses the concept’s position as both a descriptive category and a normative agenda. Employing a qualitative approach, the study draws on a literature-based inquiry and discourse analysis of academic narratives as well as public statements that have shaped, criticized, and defended the idea of Islam Nusantara. The analysis yields three main findings. First, although the term Islam Nusantara in its current usage is relatively recent and closely associated with specific intellectual networks within Nahdlatul Ulama, the plurality it invokes is rooted in a much longer historical trajectory. Second, the concept has been transformed into a normative call to renew support for, and pride in, the diversity of Islamic beliefs and practices, particularly within an increasingly competitive landscape in which religion and politics are often positioned as intensely interconnected. Third, Islam Nusantara is constrained by a tendency toward Javanese-centric framing, which may limit the expansion of its meaning and conceptual reach. This study contributes to contemporary scholarship on the history of Islam in Southeast Asia by underscoring the need to reconsider the normative relationship between Islam Nusantara and religious diversity, while also advocating a broader and more inclusive conceptual framework that accommodates historical Islamic experiences beyond Java.